Curvature‐Driven, One‐Step Assembly of Reconfigurable Smectic Liquid Crystal "Compound Eye" Lenses. Issue 9 (3rd May 2015) - Serra, Francesca; Gharbi, Mohamed A.; Luo, Yimin; Liu, Iris B.; Bade, Nathan D.; Kamien, Randall D.; Yang, Shu; Stebe, Kathleen J.
<x xml:space="preserve">Abstract</x> A self‐assembly of microlenses on a curved interface can be obtained by pinning smectic liquid crystals around a micropillar with appropriate boundary conditions. This hierarchical structure of microlenses, with variable focal lengths from a few micrometers to a few tens of micrometers, is similar to an insect's compound eye; the lenses are reconfigurable with temperature and sensitive to light polarization.